Benzodiazepine Adverse Reaction Cases Age 50 and Older Reported to the U.S. Poison Centers: Healthcare Use and Major Medical Effects - Bryan Y. Choi; Namkee G. Choi; C. Nathan Marti; S. David Baker (MDPI AG, 2024)
Background: Despite widespread consensus on the need to reduce benzodiazepine (BZD) use in older adults, prescription rates in the U.S. have paradoxically increased over the past few decades. Objective: We examined (1) the characteristics of the BZD adverse reaction cases in patients aged 50 and older that were admitted to a healthcare facility (HCF) and experienced major effects/death, and (2) the associations between the concomitant use of opioids and/or antidepressants and HCF admission and major effects/death among BZD cases. Methods: We used the 2015-2022 National Poison Data System (NPDS), which contained data from 55 America's Poison Centers. We fitted two multivariable logistic regression models to examine the associations between the co-use of opioids and/or antidepressants and HCF admission and major effects/death. Results: Of the BZD cases that were examined (N = 1979), 14.9% or 295 cases were admitted to healthcare facilities, and 8.5% of those who were followed up (77 out of 893 cases) experienced major effects or death. The number of co-used substances, co-use of opioids and antidepressants, atypical antipsychotics, anticonvulsants, muscle relaxants, and Gabapentin were associated with greater odds of healthcare admission. Co-use of opioids and healthcare admission were associated with greater odds of major effects/death. Conclusions: Adverse reactions and healthcare admissions are likely to be prevented when healthcare providers limit and carefully monitor BZD prescribing, especially for those who are on other medications, including prescription opioids and antidepressants.